Stories That Teachers Tell: Exploring Culturally Responsive Science Teaching - Jamie Wallace; Elaine V. Howes; Arthur Funk; Sean Krepski; Maya Pincus; Susan Sylvester; Kin Tsoi; Caity Tully; Raghida Sharif; Samantha Swift (MDPI AG, 2022)
In this paper, we explore the stories teachers tell as they study and grapple with culturally responsive education in their science classrooms. This qualitative case study focuses primarily on "Stories from the Field", a conversational routine at each professional learning group meeting where teachers shared observations, thoughts, and insights about their classroom, instruction, and school settings in the context of culturally responsive education. We found that teachers' stories from the first year of the group surfaced themes of navigating systemic constraints and supports, connecting through science, and sensemaking and learning from developing and analyzing strategies for culturally responsive science teaching. This helped to shine a light on a critical aspect of our work exploring culturally responsive education and what that might look like in science classrooms through the stories that teachers tell. Our findings suggest that storytelling is a rich, descriptive vehicle for exploration and sensemaking amongst teachers in a professional learning group and an underused resource in studying culturally responsive education, especially in science.